Treatment with a GPIIb/IIIa Antagonist Inhibits Thrombin Generation in Platelet Rich Plasma from Patients - Keularts, I. M. L. W.; Béguin, S.; Zwaan, C. de; Hemker, H. C. (Thrombosis and Haemostasis, 1998)
Infusion of the GPIIb/IIIa-inhibitor MK383 inhibits thrombin generation in platelet rich plasma by interfering with the production of platelet procoagulant phospholipid exposure. The effect is similar to that of 0.2 U/ml of heparin. Heparin infusion, well known to inhibit thrombin generation by fostering antithrombin activity, inhibits the formation of platelet-derived procoagulant microparticles, probably by decreasing the formation of free thrombin, which, under our circumstances, is the main platelet activator.